2013
DOI: 10.2527/jas.2012-5350
|View full text |Cite
|
Sign up to set email alerts
|

High sulfur content in corn dried distillers grains with solubles protects against oxidized lipids by increasing sulfur-containing antioxidants in nursery pigs1

Abstract: Some sources of corn dried distillers grains with solubles (DDGS) contain relatively high amounts of oxidized lipids produced from PUFA peroxidation during the production process. These oxidized lipids may impair metabolic oxidation status of pigs. The objective of this study was to understand the effects of feeding corn-soybean meal diets (CON) or diets containing 30% highly oxidized DDGS with 1 of 3 levels of supplemental vitamin E (dl-α-tocopheryl acetate), none, the 1998 NRC level (11 IU/kg), and 10x the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…However, this is not the first time that feeding distillers grains was reported to decrease lipid oxidation. Song et al (2013) also found that lipid oxidation values were not different between pigs fed 30% dried distillers grains plus solubles or corn/soybean-based control diets. One explanation for such a phenomenon is that the greater concentration of sulfur in 50% WDGS diet [0.41% vs 0.09% in 0% WDGS diet (Jolly et al 2014)] may cause an antioxidant effect.…”
Section: Lipid Oxidationmentioning
confidence: 69%
See 1 more Smart Citation
“…However, this is not the first time that feeding distillers grains was reported to decrease lipid oxidation. Song et al (2013) also found that lipid oxidation values were not different between pigs fed 30% dried distillers grains plus solubles or corn/soybean-based control diets. One explanation for such a phenomenon is that the greater concentration of sulfur in 50% WDGS diet [0.41% vs 0.09% in 0% WDGS diet (Jolly et al 2014)] may cause an antioxidant effect.…”
Section: Lipid Oxidationmentioning
confidence: 69%
“…One explanation for such a phenomenon is that the greater concentration of sulfur in 50% WDGS diet [0.41% vs 0.09% in 0% WDGS diet (Jolly et al 2014)] may cause an antioxidant effect. The high concentration of sulfur may synthesise sulfur-containing amino acids and thus alleviate the oxidative stress induced by PUFA in WDGS (Song et al 2013). Sulfur-containing amino acids such as methionine, cystine, taurine, and glutathione have been studied extensively for their antioxidant properties (Parcell 2002;Atmaca 2004;Battin and Brumaghim 2009).…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Komarnisky et al (2003) reported that sulfur-containing compounds such as cysteine, glutathione and lipoic acid protect against oxidative stress through the scavenging and reduction of various oxidants in biological systems. Some researchers found that glutathione, which is an important antioxidant that prevents damage caused by free radicals, peroxides and lipid peroxides (Pompella et al , 2003), was formed from the transsulfuration pathway during the consumption of sulfur-containing feeds (Kim et al , 2015; Song et al , 2013). Song et al (2013) demonstrated that sulfur-containing antioxidants such as glutathione enzyme, methionine and taurine were increased as fed high sulfur-containing diet to pigs.…”
Section: Resultsmentioning
confidence: 99%
“…Meat products manufactured with dietary sulfur fed animals are well known to possess significant antioxidant effects (Kim et al , 2015; Lee et al , 2009). Song et al (2013) reported that pigs that ate feed containing a high concentration of sulfur had a lot of antioxidants in their body. Additionally, supplementation with dietary sulfur is known to decrease saturated fatty acid and increase polyunsaturated fatty acid (Danielle et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SONG et al, (2013) avaliaram o desempenho de animais em crescimento e terminação com dietas a base de 0, 10, 20 e 30% de DDGS de milho. Os animais alimentados com dietas contendo 0 e 10% de DDGS tiveram desempenho equivalente, contudo, animais que receberam dietas com 20 e 30% de DDGS apresentaram GPD inferior aos demais tratamentos.…”
Section: Resultsunclassified